2014 International Conference on Medical Biometrics 2014
DOI: 10.1109/icmb.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Period Segmentation for Wrist Pulse Signal Based on Adaptive Cascade Thresholding and Machine Learning

Abstract: Wrist pulse signal has been regarded as a physical health indicator for a long history in Traditional Chinese Medicine (TCM). The quantized pulse diagnosis by using the signal processing and pattern recognition technology is introduced to take over the traditional subjective judgments in recent years, and it's attracting more and more attention. However, the previous researches with pulse preprocessing mainly concentrate on the denoising and baseline wander correction procedure. The evaluation criterion isn't … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Combining with the method of empirical mode decomposition, Xu et al proposed an adaptive wavelet threshold denoising method and showed that when the SNR was low, the denoising performance of this method was better than the traditional wavelet threshold denoising method [32]. Wang et al proposed a method based on adaptive cascade thresholding to remove the disturbance intervals and showed that an adaptive cascade threshold method could be used to obtain a stable pulse wave [33]. The above studies show that after removing interference, relatively smooth radial pulse waves can be obtained, which is beneficial to analyze the its characteristics.…”
Section: ) Noise Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining with the method of empirical mode decomposition, Xu et al proposed an adaptive wavelet threshold denoising method and showed that when the SNR was low, the denoising performance of this method was better than the traditional wavelet threshold denoising method [32]. Wang et al proposed a method based on adaptive cascade thresholding to remove the disturbance intervals and showed that an adaptive cascade threshold method could be used to obtain a stable pulse wave [33]. The above studies show that after removing interference, relatively smooth radial pulse waves can be obtained, which is beneficial to analyze the its characteristics.…”
Section: ) Noise Removalmentioning
confidence: 99%
“…The period segmentation refers to dividing a long-term waveform signal into several single-period signals according to the cardiac cycle. In the period segmentation, Wang et al accomplished it through detecting the lowest valley value as the segmentation point using the adaptive sliding window [33]. Hu et al utilized Hilbert transform to find the peak point which could be regarded as the marker of periodic segmentation [35].…”
Section: ) Period Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, we can select the less interfered periods from a pulse wave series with poor quality to complete TSA, rather than discarding the whole series (Figure 1). Similar algorithms have been applied to single-period pulse waveform extraction [14,15]. However, in existing applications, the pulse wave signal is assumed to be a strict periodic signal, and the starting point or the highest point of the waveform is used as the fiducial point for synchronization without discussing the basis of these steps.…”
Section: Introductionmentioning
confidence: 99%
“…This similarity is not the only important criterion for classifying pulse segments. Wang and Lu [ 10 ] utilized a k-nearest neighbor (KNN) classifier based on manual label data to measure the quality of the segmented single periods. However, the details and accuracy of the classifier were not shown.…”
Section: Introductionmentioning
confidence: 99%